Transnational feminism and literature : a study of women’s realities in The Lowland, Burnt Shadows and The Good Muslim - Habib, Sarah (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2015.